Technological incubators as creators of high-tech firms in Israel - Daniel Shefer; Vittorio Modena (European Regional Science Association (ERSA), 1998)
The Israeli High-Tech industry boom in the past decade deserves a thorough study of the local reality as well as an appraisal of the efficiency of existing programs. This research sets as its main objective an analysis of the effectiveness of the Incubator Program in Israel. First we evaluate the High-Tech incubators as a filter of new technological ideas that subsequently become New-Technology-Based companies. Then we discuss their efficiency and contribution to the Israeli High-Tech industry. Second, we identify the kind of investors who are willing to participate in a project during and after the incubation period. This enables us to link the incubator with other private and public sources of venture capital. Finally we analyze the geographical dispersal oft the incubators and their contribution to local economic development. For this purpose, incubators were divided into two groups, ?peripheral? and ?metropolitan?, and an extensive comparison was made of the two groups: their efficiency, relocation, and investment patterns. Our general conclusion is that although technological incubators constitute an efficient program at both the national and the local level, their wide geographical dispersal negatively affects their performance, since it contrasts with the general tendency of High-Tech industries to agglomerate. It is our belief that the number of incubators should be reduced and be more precisely located. Moreover we argue that a comprehensive High-Tech policy that includes locational considerations is needed at the national level.
Keywords: 330